Face authentication-based online voting system - Piam, Emrul Hasan; Mahmud, Ashik; Abdulghafor, Rawad Abdulkhaleq Abdulmolla; Wani, Sharyar; Abubakar, Adamu; Olowolayemo, Akeem Koye (Kulliyyah of Information and Communication Technology, 2022)
Online voting is possible and can be a lot easier than face-to-face voting because it will save money by not having to pay people to manually count votes. It can also make voting easier for people with disabilities, people who live abroad, and people who live in rural areas. Unfortunately, because of the insincerity that is found in politics and politics, doing online voting will give the dubious politicians who always try to cheat during voting a perceived chance to cheat. That is why this research proposed an online voting system that would include features such as election administration, survey administration, and facial authentication. Laravel, a PHP framework, was used to create the online voting system. Deep learning in Python was used to perform face authentication. The system that has been developed can be used to properly conduct elections, conduct surveys, make announcements, and use face authentication for identification prior to casting a ballot, among other things